A naphthalimide-based novel "Turn-On" fluorescence approach for the determination of uric acid and monitoring of xanthine oxidase activity. Issue 32 (31st July 2019) - Sidhu, Jagpreet Singh; Sharma, Shilpa; Singh, Ashutosh; Garg, Neha; Kaur, Navneet; Singh, Narinder
Abstract : Fluorescence emission of the receptor enhanced upon its binding with uric acid due to the cancellation of the PET phenomenon. Abstract : Uric acid is an important inflammatory component, which is produced by the xanthine oxidase (XO)-catalyzed reaction of xanthine. The presence of uric acid in blood serum above the normal value leads to the formation of urate crystals and causes the growth of gout. Therefore, herein, a naphthalimide-based turn-on fluorescent probe was developed to monitor the uric acid and xanthine oxidase concentration in an aqueous system. The probe exhibited high selectivity towards uric acid and the xanthine oxidase-catalyzed reaction of xanthine. The fluorescence emission of the probe was enhanced upon the binding of uric acid, generated by the XO-assisted oxidation reaction. The detection limit for xanthine oxidase was calculated to be 0.7 U mL −1 . The specificity of the probe for xanthine oxidase was confirmed by treating the enzyme with allopurinol. The endogenous images of uric acid in HeLa cells were obtained using a fluorescence microscope.